A semi-parametric survival analysis of business demography dynamics in Portugal - Nunes, Alcina (2010)
We address the post-entry performance of new Portuguese firms by investigating the structural characteristics of the hazard and survival functions, using semi-parametric survival analysis. It is based on the application of the entrepreneurship definitions and methodology of the “Manual on Business Demography Statistics” (OECD/Eurostat, 2007) to the Quadros de Pessoal dataset. The main contribution of this work is the application of a recent internationally comparable methodology for entrepreneurship to provide a multidimensional overview of firm and survival dynamics over a period of eighteen years, while guaranteeing international comparability. By correcting heterogeneity with a different specification model, we obtain stronger magnitudes of the hazard ratios found previously.